A Novel Architecture for Block Interleaving Algorithm in MB-OFDM Using Mixed Radix System - Youngsun Han; Harliman, Peter; Seon Wook Kim; Jong-Kook Kim; Chulwoo Kim (IEEE transactions on very large scale integration (VLSI) systems, 2010)
In this paper, we present a novel architecture of a block interleaver in MB-OFDM systems based on Mixed Radix System (MRS). We prove mathematically that the proposed architecture can support bit permutations in the interleaving process. The hierarchical property of our proposed MRS-based design methodology allows the proposed architecture to support all the required data rates in the MB-OFDM systems with simple modular design. Furthermore, the same design to be used for the interleaver can also be used for the operation of de-interleaving, which reduces the implementation complexity significantly. The latency of our architecture is as low as 6 MB-OFDM symbols. In addition, when comparing our proposed architecture with the conventional approach, we are able to reduce the implementation complexity by 85.5%, 69.4%, and 40.3% for 80, 200, and 480 Mb/s data rates, respectively, while improving our operating maximum clock frequency by more than 3.3 times over the conventional design. We also show that the power consumption is reduced by 87.4%, 73.6%, and 39.8% for 80, 200, and 480 Mb/s, respectively.